Leachate Treatment by Heat Treated Zeolite Media - Ragunathan, Santiagoo; Anbu Johnson, Dr.; Naimah, Ibrahim; Azlinda, Abdul Ghani; Faridah A.H. (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.